Epidemiological Trends among the Population with Chronic HCV Infection in the Netherlands. Issue 3 (April 2016) - Maan, Raoel; Toes–Zoutendijk, Esther; Veldt, Bart J; Hansen, Bettina E; Van Der Meer, Adriaan J; De Knegt, Robert J
Background: As the field of antiviral therapy for chronic HCV infection is rapidly evolving, this study aimed to assess the epidemiological changes in patient and disease characteristics among individuals with chronic HCV infection. Methods: This study included all consecutive patients with chronic HCV monoinfection who were referred between 1990 and 2013 to the Erasmus MC University Medical Center Rotterdam, a large tertiary centre in the Netherlands. To identify trends over time, the study population was divided into six equal eras based on date of first visit to the outpatient clinic. Results: A total of 1, 779 patients were diagnosed with chronic HCV infection. Mean age increased over time from 43.6 (sd 13.8) years to 51.7 (sd 11.2) years ( P <0.001). The number of patients who were referred with cirrhosis increased over time, from 31 (25%) patients in Era 1 to 118 (42%) patients in Era 6 ( P <0.001), respectively. More patients were referred with HCV genotype 1a and 3 in the last era, with 27 (48.2%) and 15 (14.0%) patients in Era 1 and 58 (54.2%) and 60 (21.8%) patients in Era 6 ( P <0.001 both), respectively. The vast majority of patients (69.5%) were born between 1950 to 1975, with 62.5% of the patients being born between 1945 and 1965. Conclusions: The HCV-infected population is ageing and is more often referred with severe liver disease. This study stresses the importance of urgently implementing national HCV screening programmes in order to be able to decrease the future burden of chronic HCV infection in the Netherlands.